2015
DOI: 10.1590/s1984-82502015000200017
|View full text |Cite
|
Sign up to set email alerts
|

Stir bar-sorptive extraction, solid phase extraction and liquid-liquid extraction for levetiracetam determination in human plasma: comparing recovery rates

Abstract: Levetiracetam (LEV), an antiepileptic drug (AED) with favorable pharmacokinetic profile, is increasingly being used in clinical practice, although information on its metabolism and disposition are still being generated. Therefore a simple, robust and fast liquid-liquid extraction (LLE) followed by highperformance liquid chromatography method is described that could be used for both pharmacokinetic and therapeutic drug monitoring (TDM) purposes. Moreover, recovery rates of LEV in plasma were compared among LLE,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 35 publications
(60 reference statements)
0
2
0
Order By: Relevance
“…however, low recoveries were observed for complex matrices. For example, Freitas-lima et al (2015) reported recoveries of 10 and 60% of an anticonvulsant drug spiked to plasma by SBSe and classical SPe, respectively, and both procedures required the same eluent volume.…”
Section: Stir Bar Sorptive Extractionmentioning
confidence: 99%
“…however, low recoveries were observed for complex matrices. For example, Freitas-lima et al (2015) reported recoveries of 10 and 60% of an anticonvulsant drug spiked to plasma by SBSe and classical SPe, respectively, and both procedures required the same eluent volume.…”
Section: Stir Bar Sorptive Extractionmentioning
confidence: 99%
“…These methods include high-performance liquid chromatography (HPLC) and gas chromatography (GC) with various detection systems [924]. Moreover, previously reported methods are mainly based on the conventional sample preparation procedure such as liquid-liquid extraction (LLE), solid-phase extraction (SPE), and plasmatic protein precipitation (PPP) [923]. The PPP procedure is considered a fast and easy method to remove the plasmatic protein; however, this procedure can result in signal suppression when liquid chromatography coupled to mass spectrometry (LC/MS) is used due to the presence of a precipitation agent, the coprecipitation of interfering species, and a lack of selectivity.…”
Section: Introductionmentioning
confidence: 99%